Pengembangan Aspek Motorik Kasar Anak Usia Dini Melalui Permainan “Arsitek Cilik” (4-5 Tahun) - Arneta Widia; Dhiva Sahillah Saragih; Nur Zakiyah; Nur Hairani Siregar (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This research focuses on the gross motor development of early childhood, particularly in the age range of 4-5 years, through the utilization of the "Little Architect" game. This phase is considered crucial in shaping the foundational physical abilities of children. Data from the Indonesian Ministry of Health indicates that a significant number of toddlers in Indonesia face developmental hindrances, including challenges in gross motor skills. With a notable prevalence, efforts are needed to design creative and stimulating programs to foster this development. This study employs a descriptive qualitative method, involving children aged 4-5 years in the "Little Architect" game. The results demonstrate that this game has a positive impact on gross motor development, involving elements such as construction and building, physical activities, collaborative play, and creativity. The implication is that "Little Architect" is not merely entertainment but also an effective and enjoyable educational tool to enhance the holistic development of early childhood.